Pengaruh Relaksasi Benson pada Nyeri Pasien Post ORIF Fraktur - Azhari, Dede Yusuf; Rivani, Dyah; Nurhidayah, Iin (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Postoperative pain of Open Reduction Internal Fixation (ORIF) fracture is a common nursing problem that affects patient recovery. Non-pharmacological interventions such as Benson relaxation technique are needed to complement analgesic therapy, reduce pain intensity through activation of the parasympathetic system and gate control theory. To evaluate the effectiveness of Benson relaxation technique on reducing pain scale in post-ORIF clavicle fracture patients in Al-Fath Ward, PKU Muhammadiyah Bantul Hospital. A descriptive case study on a male patient (31 years old) with a closed fracture of the left clavicle after ORIF, conducted on February 17–20, 2026. Pain measurement using the Numeric Rating Scale (NRS) before and after the 3-day intervention (10–15 minutes/session, 1 hour before analgesics) via interviews, informed consent, and independent practice. The pain scale decreased gradually: Day 1 (pre=5, post=4), Day 2 (pre=4, post=3), Day 3 (pre=3, post=2). Patients reported increased comfort after the intervention. Conclusion: The Benson relaxation technique is effective as a stand-alone non-pharmacological intervention to reduce post-ORIF fracture pain, with rapid patient adaptation.